The Oxford handbook of the Italian economy since unification - Toniolo, Gianni, 1942- (New York : Oxford University Press, 2013)
'The Oxford Handbook of the Italian Economy Since Unification' provides, for the first time, a comprehensive, quantitative 'new economic history' of Italy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Italy -- Economic policy; Italy -- Economic conditions